Estimation of Maneuvering Coefficients of the KCS Using Captive Model Test Simulations in the OpenFOAM Framework - Minsu Cho; Theo Descamps; Benjamin Bouscasse; Young-Myung Choi (한국해양공학회지, 2025)
The accurate prediction of ship maneuvering performance is crucial for ensuring maritime safety and operational efficiency. With increasing ship sizes and complex operating conditions, more advanced computational tools are increasingly required. In this study, an OpenFOAM-based in-house solver called foamStar was validated for predicting the hydrodynamic maneuvering behavior of the KRISO Container Ship. A Reynolds-averaged Navier–Stokes equation model combined with a volume-of-fluid approach was employed to capture free-surface effects. A moving mesh method was adopted to solve prescribed ship motions. Simulations were conducted for oblique towing and rotating arm tests under various drift angles and yaw rates, and a mesh convergence study was performed using coarse, medium, and fine meshes. The results showed that the computed sway forces and yaw moments agreed closely with experimental data and numerical benchmarks, and the estimated linear hydrodynamic coefficients closely matched experimental measurements. However, the nonlinear hydrodynamic coefficients require the computations with fine mesh to have similar values with experimental results. In conclusion, foamStar is a reliable tool for accurately predicting hydrodynamic maneuvering coefficients when employing a sufficiently refined mesh.